PENGGUNAAN MODEL ALTMAN Z”-SCORE, SPRINGATE, ZMIJEWSKI UNTUK MEMPREDIKSI FINANCIAL DISTRESS PERUSAHAAN PERTAMBANGAN LISTING BEI - Iman Indrafana Kusumo Hasbullah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2021)
This research aims to analyze the results of financial distress prediction using the methods of Altman Z "-Score, Springate, and Zmijewski. This research uses secondary data, that is financial reports from mining company data that listed in Bursa Efek Indonesia (BEI) years 2010 - 2016. The total of all mining companies in this research are 42 companies and there are 26 companies that use as samples. Sample selectied by purposive sampling. Data analysis techniques in this research using quantitative descriptive analysis technique.. Research results, there were 7 companies that predicted in healthy condition by using the method of Altman Z "-Score. There were 2 companies that were predicted in healthy condition by using Springate method and by using Zmijewski method, there were as many as 12 companies were predicted in healthy condition. For predictions of companies that were in bankruptcy condition, Altman Z "-Score method predicts there were as many as 2 companies that were in bankrupt condition. By using Springate method, there were as many as 6 companies in a state of bankruptcy were predicted. By using Zmijewski method, there were as many as 1 company predicted in a state of bankruptcy. For the overall results of each methods, there were two companies that were in a healthy condition for 7 consecutive years, consistent with the results that predicted by each methods, there were the method of Altman Z "-Score, Springate, and Zmijewski.